2011
DOI: 10.3389/fphys.2011.00103
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Extracellular Matrix Proteins Influence Angiogenesis and Lymphangiogenesis in Mouse Embryoid Bodies

Abstract: Regulatory mechanisms for angiogenesis are relatively well established compared to lymphangiogenesis. Few studies have shown that a combination of vascular endothelial growth factor VEGF-A/C with hypoxia or collagen matrix promotes lymphatic structures along with blood vessel development in mouse embryoid bodies (EB). In this study we tested the hypothesis that while hypoxia combined with prolonged VEGF-A/C treatment would induce early lymphangiogenesis in addition to angiogenesis in mouse EBs, under similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Membrane-associated proteins that utilize palmitoylation to increase hydrophobicity for impacting cell motility or membrane trafficking could be suitable targets for novel therapeutics in metabolic syndrome and type 2 diabetes. We identified several appropriate candidates including FBLN3 (fibulin-3), which associates with the extracellular matrix and promotes cell migration 21 , 22 , LYVE1 (Lymphatic vessel endothelial hyaluronic acid receptor 1 23 , BST2 (Bone marrow stromal antigen 2) 24 , and PAFAH1b3 25, 26 (pursued in detail below).…”
Section: Resultsmentioning
confidence: 99%
“…Membrane-associated proteins that utilize palmitoylation to increase hydrophobicity for impacting cell motility or membrane trafficking could be suitable targets for novel therapeutics in metabolic syndrome and type 2 diabetes. We identified several appropriate candidates including FBLN3 (fibulin-3), which associates with the extracellular matrix and promotes cell migration 21 , 22 , LYVE1 (Lymphatic vessel endothelial hyaluronic acid receptor 1 23 , BST2 (Bone marrow stromal antigen 2) 24 , and PAFAH1b3 25, 26 (pursued in detail below).…”
Section: Resultsmentioning
confidence: 99%
“…. Induction of either angiogenesis or lymphangiogenesis from embryoid bodies depending on control of the local chemical environment also highlights the common lineage between lymphatic and blood endothelial cells. These examples of lymphatic/blood endothelial cell plasticity and our observation of lymphatic/blood vessel connections in cultured rat mesenteric tissues motivate future studies using the rat mesentery culture model to determine whether cell plasticity in an intact microvascular network scenario leads to conversion of vessel types.…”
Section: Discussionmentioning
confidence: 98%
“…In breast cancer, increased LVD, lymph node involvement, and lymph vessel invasion are predictive of higher risk of metastasis; further, increased LVD and lymph node metastasis are commonly observed in PPBC [16] . While the role of collagen in lymphangiogenesis has not been extensively characterized, one study has shown that collagen I increases lymphangiogenesis and angiogenesis in mouse embryoid bodies under hypoxic conditions [160] . Therefore, it is plausible that other fibrillar collagens may contribute to lymphangiogenesis during mammary tumorigenesis.…”
Section: Endothelial Vessel Formationmentioning
confidence: 99%